Determining the structural features of the chromium and copper alloy material obtained by electron beam welding - Vrzhyzhevskyi, Eduard; Kostin, Valery; Taranova, Tatjana; Zvorykina, Anastasiia; Zvorykin, Volodymyr; Zvorykin, Leonid (Eastern-European Journal of Enterprise Technologies, 2025)
This study considers a welded joint between copper and chromium. The task addressed is to enable the formation of a copper and chromium joint based on the selection of the alloy material’s optimal structure. Based on scanning electron microscopy, micro-X-ray spectral analysis, and microhardness measurement, the properties of the welded joint material in a copper and chromium joint were investigated. The joint was obtained by electron beam welding by preheating one of the metals while removing additional heat supply from the other. It was established that a moving electron beam leads to the formation of different types of microstructure in the alloy material with significant concentration heterogeneity: quasi-dendritic; linearly elongated; scaly; cellular; quasi-spherical. Welding with a stationary, linearly deployed along the joint, electron beam with preheating of one of the metals and providing additional heat removal from the other enables the formation of a concentrically uniform weld with a quasi-spherical microstructure of copper-chromium eutectic. The directional nature of the copper-based grains, which are elongated in the direction across the welded joint, which corresponds to the direction of additional heat removal from one of the welded metals, was revealed. The material obtained by a stationary, linearly deployed along the joint, electron beam under the mode Uacc = 60 kV, Ieb = 40 mA, P = 5·10-3 Pa for a duration of 7 seconds with preheating of chromium to 900°C and providing additional heat removal from copper was determined as the alloy material of the welded joint between copper and chromium with an optimal structure. The results could be used while making copper-chromium joints by fusion welding in a vacuum with regulation of the speed of movement and focusing of the source of thermal energy supply